Intensive Motivational Interviewing for Heavy Drinking Among Women. (June 2019) - Polcin, Douglas L.; Korcha, Rachael; Pugh, Sheila; Witbrodt, Jane; Salinardi, Michelle; Galloway, Gantt; Nayak, Madhabika B.; Nelson, Emily
Abstract : Objectives: Women suffer more severe consequences related to heavy drinking than men. Relative to men, women who are heavy drinkers experience higher severity of medical, psychiatric, and social problems, even when they have fewer years drinking. Currently there are few sex-specific, evidence-based interventions for heavy drinking among women. Methods: A randomized clinical trial was conducted with 215 women with alcohol problems. Half were randomly assigned to receive a 9-session, "intensive motivational interviewing" (IMI) intervention (N=107) and half were randomly assigned to a single session of standard motivational interviewing along with 8 sessions of nutritional education (N=108) to achieve time equivalence. Both conditions received weekly outpatient group counseling. Follow-up interviews were conducted at 2 months. Primary outcomes included percent drinking days (PDD), percent heavy drinking days (PHDD, 4+ drinks), and the Addiction Severity Index Alcohol scale. Longitudinal changes were assessed using generalized estimating equations. Results: The sample was predominantly white (83.3%), college educated (61.4%), and married (53.5%). The mean age was 50.9 (SD=11.3). Relative to baseline, both study conditions show significant reductions in percent drinking day, PHDD, and Addiction Severity Index alcohol severity ( P <0.001). Among heavy drinkers, defined as women drinking 14+ days to the point of intoxication over the past 30 days at baseline (N=153), those assigned to IMI (n=67) showed larger reductions in PDD ( P <0.01) and PHDD ( P <0.05) at 2 months compared to women receiving standard motivational interviewing. Conclusions: Findings support the efficacy of IMI for heavy drinking among women. Additional studies are needed that assess drinking over longer time periods.